Spontaneous Coronary Artery Dissection Clinical Review: Current State of Evidence and Challenges Ahead - Halabi, Zain R.; Garcia, Ronald T.; Schreiber, Theodore L.; Kaki, Amir (International Journal of Angiology, 2025)
Spontaneous coronary artery dissection (SCAD) has been increasingly recognized as a potentially serious nonatherosclerotic condition that can mimic atherosclerotic acute coronary syndromes. This condition has been identified as presenting with the classical clinical and electrocardiographic features that are encountered with acute coronary syndromes. Its formal identification has been historically challenging and difficult. A high index of clinical suspicion before invasive coronary angiography depends on the presence of some inherited and acquired risk factors. Early suspicion plays a key role in the identification of SCAD lesions during coronary angiography. Multiple angiographic features may be present, thus resulting in different types of SCAD lesions. Acute SCAD management favors conservative approaches for stable cases, with revascularization for high-risk presentations. Pharmacotherapy typically includes antiplatelet agents and β-blockers, avoiding routine anticoagulation. Long-term care involves recurrence prevention, monitoring, counseling, and screening for extra coronary fibromuscular dysplasia. Significant areas of uncertainty remain, as this relates to the best long-term management and surveillance strategies. This review aims to summarize the current state of knowledge and evidence, while pointing out the remaining challenges and the need for additional research.
Keywords: SCAD; dissection flap; intramural hematoma; fibromuscular dysplasia